Percepción de los efectos económicos, financieros y sociales de la reforma al cálculo del anticipo al impuesto a la renta y la exoneración del anticipo al impuesto a la renta por cinco años para toda inversión nueva, y su real aprovechamiento en las pequeñas y medianas empresas en el sector textil del Distrito Metropolitano de Quito en los años 2011 y 2012. - Collaguazo Troya, Verónica Elizabeth (2015)
The Organic Code of Production, Trade and Investment, issued December 29, 2010 shows the creation of a legal framework conducive to productive sector which can enhance national and international investment and provide support to sectors that contribute mainly to change productive matrix of the country. PYMES in our country are in particular in the production of goods and services and is the basis of social development producing both demanding and buying products or adding value and therefore constitute a key player in the generation of wealth and employment. This paper presents research analyzing the perception of economic, financial and social effects of the reform to the calculation of the payment of income tax and the exemption from payment to income tax for five years for any new investment, and its actual use in small and medium enterprises in the textile sector of the metropolitan district of Quito in 2011 and 2012.